Applied graph- theoretic approach for two- way to one- way road network conversion - Tan, Kok Chuen (2008)
It is not uncommon in the field of traffic engineering for two-way roads to be converted to one-way roads and vice versa. In these situations the traffic engineer would be faced with the problem of selecting direction for each of the one-wayroads. This problem is named the one-way road network problem in this thesis. By modelling the road networks as graphs, analgorithm(called 'conversion algorithm' in this thesis) is developed; this enables the search for a global optimal solution for the given road network (based on a theoretical efficiency criterion) by means of enumeration, or exhaustive listing of solutions.